Polarized retinal pigment epithelium generates electrical signals that diminish with age and regulate retinal pathology. Issue 11 (30th August 2018) - Cao, Lin; Liu, Jie; Pu, Jin; Milne, Gillian; Chen, Mei; Xu, Heping; Shipley, Alan; Forrester, John V; McCaig, Colin D; Lois, Noemi
Abstract: The transepithelial potential difference (TEP) across the retinal pigment epithelial (RPE) is dependent on ionic pumps and tight junction "seals" between epithelial cells. RPE cells release neurotrophic growth factors such as pigment epithelial derived factor (PEDF), which is reduced in age‐related macular degeneration (AMD). The mechanisms that control the secretion of PEDF from RPE cells are not well understood. Using the CCL2/CX3CR1 double knockout mouse model (DKO), which demonstrates RPE damage and retinal degeneration, we uncovered an interaction between PEDF and the TEP which is likely to play an important role in retinal ageing and in the pathogenesis of AMD. We found that: (a) the expression of ATP1B1 (the Na + /K + ‐ATPase β1 subunit) was reduced significantly in RPE from aged mice, in patients with CNV (Choroidal Neovascularization) and in DKO mice; (b) the expression of PEDF also was decreased in aged persons and in DKO mice; (c) the TEP across RPE was reduced markedly in RPE cells from DKO mice and (d) an applied electric field (EF) of 50‐100 mV/mm, used to mimic the natural TEP, increased the expression and secretion of PEDF in primary RPE cells. In conclusion, the TEP across the RPE depends on the expression of ATP1B1 and this regulates the secretion of PEDF by RPE cells and so may regulate the onset of retinal disease. Increasing the expression of PEDF using an applied EF to replenish a disease or age‐reduced TEP may offer a new way of preventing or reversing retinal dysfunction.